The Ark and the Dove : the story of Noah's wife - Smith, Jill Eileen, 1958- (Revell, a division of Baker Publishing Group, 2024)
"Only Noah and his family know that God's judgment is coming soon. He and his wife Emzara dedicate themselves to God's command to build an ark. After years of preparing for the end of life as they know it, can they survive what lies ahead or will they simply relive the past they are trying to escape?"--